2018
DOI: 10.1186/s12934-018-1017-5
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant production and hydrocarbon degradation activity of endophytic bacteria isolated from Chelidonium majus L.

Abstract: BackgroundThe process of plant growth in the contaminated environment is often inhibited and entails the neutralization of harmful compounds. To reduce the negative impact of harmful compounds microorganisms produce unique compounds called biosurfactants. This paper describes the potential of culturable endophytic microorganisms from synanthropic plant-Chelidonium majus L. for the production of biosurfactants, as indirect plant promoting factors as well as their degradation activity. Emulsifying activity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…In comparison to chemical surfactants, biosurfactants possess lower toxicity, higher biodegradability and environmental compatibility, and can be produced from regenerated biomass resources and industrial by-products [7]. Therefore, in addition to classical cleaning applications, they have promising applications in environmental protection, crude-oil recovery, food-processing, biofilm prevention and disruption, and in various fields of biomedicine [810]. Glycolipids are a group of the most common biosurfactants and mainly consist of sophorolipids, mannosylerythritol lipid, cellobiose lipids, liamocins and polyol esters of fatty acids [4].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to chemical surfactants, biosurfactants possess lower toxicity, higher biodegradability and environmental compatibility, and can be produced from regenerated biomass resources and industrial by-products [7]. Therefore, in addition to classical cleaning applications, they have promising applications in environmental protection, crude-oil recovery, food-processing, biofilm prevention and disruption, and in various fields of biomedicine [810]. Glycolipids are a group of the most common biosurfactants and mainly consist of sophorolipids, mannosylerythritol lipid, cellobiose lipids, liamocins and polyol esters of fatty acids [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, diesel oil constitutes a complex mixture of hundreds of aromatic hydrocarbons, predominantly iso-alkanes, paraffinic, olefinic, naphtha and aromatic compounds (Yakimov et al, 2005) while used engine oil contains a variety of recalcitrant compounds, like alkyl benzenes, naphthalenes, methylnaphthalenes, PAHs and metals (Dominguez-Rosado and Pitchell, 2003;Lu and Kaplan, 2008). Marchut-Mikolajczyk et al (2018) reported that B. pumilus 2A was an effective hydrocarbon degrader of both diesel oil and waste engine oil but exhibited different degree of diesel oil and engine oil degradation. In addition, 2A strain showed different degradation efficiency of each hydrophobic component found in the two petrochemical products.…”
Section: Discussionmentioning
confidence: 99%
“…Recalcitrant hydrocarbon (present in engine oil) degrading microbes of genus Bacillus produce biosurfactants of a diverse chemical nature and molecular size, with different active role(s). These microbial biosurfactants have the capability to degrade hydrocarbons enhancing the bioavailability of hydrophobic organic compounds in engine oil [ 8 ]. In recent era, biosurfactants have received special attention due to their unique properties like biodegradability, eco-friendly and low toxicity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%